Persepsi Wisatawan Milenial Terhadap Akomodasi Glamping di Kawasan Kintamani - Juniarta, Pande Putu; Wardana, Miko Andi; Saputra, Kadek Wira Adi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
Glamorous Camping or known as Glamping is a new trend in traveling. Glamping has emerged as a global trend in outdoor tourism. The Glamping trend emerged with the increasing tourist demand for comfort and luxury in the nature-based tourism sector. The millennial generation is relatively braver when traveling if compared to the previous generation, commonly known as generation X. Generation X prefers travel with the aim of relaxation, it is contrast to the millennial generation who prefers challenges. This study aims to determine the perception of millennial tourists towards glamping accommodation in the Kintamani area. The method used in this study is a quantitative descriptive method where data is obtained through a questionnaire with five indicators related to glamping accommodation including glamping facilities, glamping cleanliness, environment and landscape, glamping management services and interior design and glamping buildings. The results showed that millennial tourists responded with a value of 4.46 which was in a very good interval. In future development, it is necessary to suggest special training for the staff in each glamping area in the Kintamani area, additional parking areas and arrangement of access to the glamping area and the need for data collection on each glamping accommodation in the Kintamani area. Keyworsd: Glamping, Perception, Millenial Tourist, Alternatif Acommodation